The Effectiveness of Using Jennierubyjane as a Medium in Improving Student Speaking Skill - Nadia Alfaini; Lidiyatul Izzah; Siti Aminah (English Language in Focus (ELIF), 2023)
Currently, the most widely spoken language worldwide is English. In social settings, at work and at school, millions of people use English as their primary language of communication. It is important to teach students to speak English as a foreign language in the classroom. A teacher should be able to create a more interesting and effective classroom learning atmosphere, then looking at the progress of how well students can communicate in a language is often used to assess the effectiveness of a language learning program. Students must demonstrate speaking fluency as well as the ability to articulate their thoughts and knowledge in a specific type of text for speaking skills. To find out whether Jennirubyejane's vlog videos can improve students' speaking learning, this study divided two classes into a control group and an experimental group and collected data using quantitative pre-test and post-test methodology. The purpose of educational media is to stimulate students' knowledge of facts, skills and thought processes. As a result, audio-visual media has a good impact that promotes language acquisition by being helpful and stimulating to assist English language learning and the results show that Jennierubyjane's vlog videos are a useful medium for teaching speaking.